AKIBAT HUKUM PENERIMA DANA LAYANAN PENDANAAN BERSAMA BERBASIS TEKNOLOGI INFORMASI GAGAL BAYAR (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2023)
Technological innovations with financial features continue to emerge, marking the momentum of transformation in the financial world. Fintech Lending or Fintech Peer to peer Lending is a money lending and borrowing service in the financial sector with the use of information technology, this type provides loans for people's urgent needs. This technology-based financial service offers financial products that provide hope for people who need money. The effects that occur are problems for recipients of online loan funds because they are unable to pay so they are trapped in debt and the risk of defaulting on loans or known as